Marginal formations of the last Kara and Barents ice sheets in northern European Russia. - Astakhov, Valery I; Svendsen, John Inge; Matiouchkov, Alexei; Mangerud, Jan; Maslenikova, Olga; Tveranger, Jan (PANGAEA, 1999)
Glacial landforms in northern Russia, from the Timan Ridge in the west to the east of the Urals, have been mapped by aerial photographs and satellite images supported by field observations. An east-west trending belt of fresh hummock-and-lake glaciokarst landscapes has been traced to the north of 67°N. The southern boundary of these landscapes is called the Markhida Line, which is interpreted as a nearly synchronous limit of the last ice sheet that affected this region. The hummocky landscapes are subdivided into three types according to the stage of postglacial modification: Markhida, Harbei and Halmer. The Halmer landscape on the Uralian piedmont in the east is the freshest, whereas the westernmost Markhida landscape is more eroded. The west- east gradient in morphology is considered to be a result of the time-transgressive melting of stagnant glacier ice and of the underlying permafrost. The pattern of ice-pushed ridges and other directional features reflects a dominant ice flow direction from the Kara Sea shelf. Traces of ice movement from the central Barents Sea are only discernible in the Pechora River left bank area west of 50°E. In the Polar Urals the horseshoe-shaped end moraines at altitudes of up to 560 m a.s.l. reflect ice movement up-valley from the Kara Ice Sheet, indicating the absence of a contemporaneous ice dome in the mountains. The Markhida moraines, superimposed onto the Eemian strata, represent the maximum ice sheet extent in the western part of the Pechora Basin during the Weichselian. The Markhida Line truncates the huge arcs of the Laya-Adzva and Rogovaya ice-pushed ridges protruding to the south. The latter moraines therefore reflect an older ice advance, probably also of Weichselian age. Still farther south, fluvially dissected morainic plateaus without lakes are of pre-Eemian age, because they plunge northwards under marine Eemian sediments. Shorelines of the large ice-dammed Lake Komi, identified between 90 and 110 m a.s.l. in the areas south of the Markhida Line, are radiocarbon dated to be older than 45 ka. The shorelines, incised into the Laya-Adzva moraines, morphologically interfinger with the Markhida moraines, indicating that the last ice advance onto the Russian mainland reached the Markhida Line during the Middle or Early Weichselian, before 45 ka ago.
Reconstructed ice-sheet limit in the Kara and Barents Sea area at about 50,000 years ago (Markhida Line)
Keywords: AGE; Ice extent; MarkhidaLine; Quaternary Environment of the Eurasian North; QUEEN; QUEENModels; RECON; Reconstructed; Reconstructed data